Efektifitas Model Pembelajaran Blended Learning Dengan Pendekatan STEM Terhadap Kemampuan Berfikir Kritis Siswa Di SMA IT TGH UMAR Kelayu Tahun 2021/2022 - Rizal Umami (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
In its development, information technology has encouraged efforts to reform teaching methods in education, so it needs to be applied in the world of education. Indonesia is at number 396 science performance abilities which are classified as low, especially in the ability to think critically. The purpose of this research is to find out whether the blended learning model with the STEM approach is effective in improving students' critical thinking skills, so it is necessary to bring up learning innovations, such as the blended learning model with the STEM approach, which is expected to be able to improve students' critical thinking skills. Based on the research results obtained in the experimental class that students' critical thinking skills are higher than in the classical control class, namely 82.20 and 63.60, so based on these data it can be concluded that the blended learning model with the STEM approach can improve students' critical thinking skills